A Cross Sectional Study of Intern’s Willingness to Serve in Rural Primary Health Centres of Andhra Pradesh, India. - Shakeel Anjum,; Naveen Karbhari,; P. Parthasarathi Reddy,; Monica M,; Yadavrao,; Cauvery K, (Universiti Kebangsaan Malaysia, 2013)
The shortage of health professionals in rural areas is a global problem. The urban and rural maldistribution of doctors results in severe problems regarding access to and performance of health care services. Retaining doctors in rural areas is a challenging task for a number of reasons, ranging from personal preferences to difficult work conditions and low remuneration.